Prevalence and Mortality of Sarcopenia in a Community-dwelling Older Japanese Population: The Hisayama Study - Nakamura, Kimitaka (J Epidemiol, 2021)
BACKGROUND: The prevalence of sarcopenia defined using the Asian Working Group for Sarcopenia (AWGS) criteria in Asian communities has not been fully addressed. Moreover, few studies have addressed the influence of sarcopenia on mortality. METHODS: A total of 1,371 and 1,597 residents aged 65 years or older participated in health surveys in 2012 and 2017. Sarcopenia was determined using the AWGS definition. Factors associated with the presence of sarcopenia were assessed using a logistic regression model in participants in the 2012 survey. Subjects in the 2012 survey were followed-up prospectively for a median of 4.3 years. Mortality risk for subjects with sarcopenia was examined using the Cox proportional hazards model. RESULTS: The crude prevalence of sarcopenia was 7.4% and 6.6% in participants at the 2012 and 2017 surveys, respectively; there was no significant difference between surveys (P = 0.44). The prevalence of sarcopenia increased significantly with age in both sexes (both P for trend <0.001). Subjects with sarcopenia were more likely to exercise less regularly, to intake less total energy, and to exhibit a disability in activity of daily living than those without. The multivariable-adjusted hazard ratio for all-cause mortality was 2.20 (95% confidence interval, 1.25–3.85) in subjects with sarcopenia, compared to those without. CONCLUSIONS: Approximately 7% of older subjects had sarcopenia in a community-dwelling older Japanese population. Moreover, subjects with sarcopenia had an increased mortality risk. Our findings suggest that a public health strategy for sarcopenia is needed to extend healthy life expectancy.